Earth science in the city : a reader - Heiken, Grant; Fakundiny, Robert H.; Sutter, John F.; Wiley eBooks (Washington, DC : American Geophysical Union, 2003)
With half of the Earths people now living in cities, our capacity to understand and resolve urban issues has global implications. For urban geoscientists, researchers, and students of cities.
Large urban concentrations / George Bugliarello -- Geoantiquities in the urban landscape / Marjorie A. Chan [and others] -- Engineering geology of New York City / Charles A. Baskerville and Robert H. Fakundiny -- Towards integrated natural hazard reduction in urban areas / Greg A. Valentine -- Seismic-risk evaluation in cities of New York and surrounding regions / Robert H. Fakundiny -- Facing volcanic and related hazards in the Neapolitan area / Giovanni Orsi [and others] -- Tsunami impact and mitigation in inhabited areas / G.T. Hebenstreit, F.I. Gonzalez and J. Preuss -- Landslides and cities / Richard J. Pike, David G. Howell and Russell W. Graymer -- Effects of urbanization on groundwater systems / J.M. Sharp, Jr. [and others] -- Integrated environmental modeling of the urban ecosystem / Timothy N. McPherson [and others] -- Urban environmental modeling and assessment using detailed urban databases / Steven J. Burian [and others] -- Mapping the city landscape from space / Michael S. Ramsey -- Airborne laser topographic mapping / Dean Whitman [and others] -- Integrating geological information into urban planning and management / B.R. Marker, J.J. Pereira and E.F.J. de Mulder -- Greater Phoenix 2100 / Jonathan Fink [and others] -- Modeling cities, the Los Alamos urban security initiative / Grant Heiken [and others].
Includes bibliographical references.
John Wiley and Sons
Keywords: Urban geology; Urban geology; Electronic books